Aggressive Behavior Of Early Children In The Kindergarten Of Bina Tunas Bangsa Batang Hari Regency Jambi Province - Asti, Dwi; Yudha, Rivo Panji (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study discusses the phenomenon of aggressive behavior in children in educational institutions, especially in PAUD, with a focus on group B at Bina Tunas Bangsa Kindergarten. The purpose of this study is to help teachers understand and handle aggressive behavior in children effectively, so as to prevent further impacts that have the potential to become criminal acts. The study found that aggressive behavior is often triggered by teasing in class or while playing, which causes two types of aggression: physical (such as hitting and kicking) and verbal (insults or using bad words). This study uses a qualitative approach with a case study method. Some of the proposed handling strategies include understanding the child's personality, creating an active and enjoyable learning environment (PAKEM), channeling aggression through positive activities, avoiding rewards for aggressive behavior, and using non-physical positive punishment. Strategies for handling children with aggressive behavior at Bina Tunas Bangsa Kindergarten include understanding and accepting the child's personality, creating PAKEM (Active, Creative, Effective and Enjoyable Learning), achieving cataracts (channeling aggressive behavior into positive activities), eliminating rewards, Demonstration/training strategies, creating a non-aggressive environment and positive punishment (not physical punishment).